Client and service factors associated with changes in health-related quality of life following community rehabilitation. Issue 3 (30th January 2023) - Snowdon, David A.; McGill, Scott; Altmann, Christie; Brooks, Kathryn; Everard, Tori; Le Fevre, Kate; Andrew, Nadine E.
Abstract: Purpose: To identify client and service factors associated with changes in health-related quality of life following community rehabilitation. Methods: We conducted a retrospective observational cohort study within a community rehabilitation program. Health-related quality of life was measured using the EuroQol five Dimensions, five response level version (EQ-5D-5L). Our primary outcome was the Visual Analogue Scale (VAS) rating of overall health. Analyses were stratified by diagnostic group: traumatic orthopaedic, elective orthopaedic, neurological, medical, and other. The association between client and service factors and discharge VAS scores, adjusted for baseline scores were determined using multivariable regression. Results: EQ-5D-5L data were available for 981 of 1350 participants. Treatment intensity was associated with a seven-point increase ( β = 7.22, 95%CI 2.28–12.2, p = 0.004) in VAS scores for traumatic orthopaedic participants. For neurological participants, there was a positive interaction between comorbidities and intensity of therapy ( β = 7.9, 95%CI 2.75–13.1, p = 0.003), indicating that greater therapy intensity in those with higher comorbidity scores was associated with an improvement in VAS scores. Age was negatively associated with VAS scores for traumatic orthopaedic participants and socioeconomic status was positively associated with VAS scores for elective orthopaedic participants. Conclusions: Treatment intensity is a modifiable service factor that may positively influence health-related quality of life. Implications for rehabilitation: In addition to providing information on client progress towards attainment of individual treatment goals, routine collection of patient reported outcome measures within a community rehabilitation program can elicit information that can inform rehabilitation service improvement. Clients of a community rehabilitation program with a neurological or medical condition demonstrate the least improvement in overall health profile and may require additional rehabilitation or supports. Across all diagnostic groups, problems with anxiety and depression were least likely to improve following receipt of community rehabilitation. Improving access to psychological services and associated referral pathways in community rehabilitation services could improve these outcomes. Initiatives aimed at increasing intensity of therapy such as targeted triage and resource allocation, may improve health-related quality of life for clients of a community rehabilitation program with traumatic orthopaedic conditions. For clients with a neurological condition, initiatives aimed at increasing intensity of therapy may improve health-related quality of life in more complex patients with comorbid health conditions.